Development and evaluation of the psychometric properties of a digital questionnaire for the evaluation of perinatal psychosocial needs - Paola Bully; Isabel Artieta-Pinedo; Carmen Paz-Pascual; Arturo García-Álvarez; Ema-Q Group; Maite Espinosa (BMC, 2023)
Abstract Background If the purpose of maternal education is for women to take control of their own health and that of their family in the process, it is essential to have a simple instrument that allows them to self-assess, globally, how prepared they are to face future childbirth and maternity. As there is nothing similar in our area, the objective of this study was to design a complete, specific measurement questionnaire, with good metric quality and in digital format, for the assessment of perinatal psychosocial needs. Methods A cross-sectional study was carried out, to evaluate the psychometric properties of a digital measurement questionnaire. The questionnaire was developed in 4 steps following the recommendations of the International Test Commission. The participants were 263 pregnant women who were recruited in primary health care appointments in the Basque Healthcare Service (Osakidetza); they completed the newly created questionnaire and all the test selected as gold standard. Their mean age was 33.55 (SD = 4.73). The analysis of the psychometric characteristics was based on mixed expert judgment procedures (focus group of healthcare professionals, item assessment questionnaire and interviews with users) and quantitative procedures (EFA, CFA, association with the gold standard and classification agreement index, ordinal alpha and McDonald's omega). Results The final version of the questionnaire was made up of 55 items that evaluate 8 aspects related to perinatal psychosocial well-being (anxious-depressive symptoms, pregnancy acceptance, partner support, coping, internal locus of control, childbirth self-efficacy, perception of childbirth as a medicalized event, and fear of childbirth). Various tests were made of the validity and reliability of the scores, providing metric guarantees for their use in our context. Conclusions The use of this complete, quick-to-use tool with good psychometric properties will allow pregnant women to take stock of their situation, assess whether they have the necessary resources in the psychological and social sphere, and work together with midwives and other health professionals in the areas that are lacking.